MENINGKATKAN WAWASAN MAHASISWA PRA-SKRIPSI TENTANG MANAJEMEN REFERENSI OTOMATIS BERBASIS MENDELEY - Oktaviyanti, Itsna; Maulyda, Mohammad Archi; Amrullah, Lalu Wira Zain; Nurmawanti, Iva; Erfan, Muhammad (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of these community services activities was to solve the problem of writing references and bibliography for students who start writing their thesis. To achieve this purpose, community service is carried out in several stages, namely the preparation of webinars, Mendeley-based Automatic Reference Management webinars and evaluation of webinar activities. Preparation of webinar activities including coordination, preparation of zoom accounts and flyers for students, then the Mendeley-based Automatic Reference Management webinar as the core activity of this community service. The webinar evaluation is carried out by posttest. The service activities that have been carried out are considered successful shown by activities that have been done, the enthusiasm of the participants is quite high and the insight into writing references and making student bibliography increases. This is evident from the time the webinar activity was according to plan, the webinar participants reached 96 students and the posttest results showed that students' understanding of automatic reference management had increased by up to 77.5%.